I. Kant’s Apriorism and Development of Analytical Philosophy - Nekrašas, Evaldas (Problemos, 1975)
An attempt is made in the paper to investigate theoretical prerequisites of the Kantian apriorism and to determine its significance for the development of analytical philosophy. One of the main problems of Kant’s epistemology was the proof of apodeicticity of the laws of the Newtonian mechanics. Therefore changes in interpretation of these laws are analysed from phenomenalism to essentialism; Kant follows the tradition of essentialism in the proof of apodeicticity. Kant’s analysis of mathematical theories appears to be but a systematization of traditional views. Changes of understanding of the role of conceptual apparatus in the analytical philosophy are discussed. The conclusion is drawn that, though analytical philosophy constitutes itself in radical opposition to the Kantian apriorism, the aprioristic tendencies do appear and get stronger in the course of its development. The conceptual apriorism of the analytical philosophy is more radical than that of the Kantian: the place of the one and nonhistorical transcendental subject is overtaken by plurality of nonconstant and noncomparable conceptual systems.